Analysis Of Moral Message On “Demi Lovato” Songs Lyrics - Marsela; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
Background: While discussing a song's lyrics, the ability of the music to convey emotion immediately comes to mind. Usually, a song's lyrics give an account of the feelings or thoughts that go into it. Inspirational lyrics are good lyrics. Whether a song has an impact on the listener's ears depends on the phrases that make up the song. Rahim (2019) asserts that a word, expression, or sign that refers to or represents something and can be described in other words constitutes the meaning of music lyrics. Methodology: Research that is descriptive and frequently uses analysis is called qualitative research. According to Creswell (2014), the research design employed in this study is qualitative research. This is because the purpose of the research is to determine the meaning behind the lyrics of a song by Demi Lovato. Findings: The findings in this study are to answer the researcher's questions, the researcher listens or reads the song lyrics thoroughly and the data results are taken from the process of analyzing the moral message in the album